Venous thromboembolism risk assessment in hospitalised patients: A new proposal (Clinics, 2013)
OBJECTIVE: Cross-sectional studies have been conducted to evaluate the adequacy of prophylaxis for venous thromboembolism. However, these studies often evaluate prophylaxis on the data collection day, without analysing the prophylactic dose or duration and without reference to inappropriate use in patients without risk. A prospective, observational study was performed to assess the adequacy of prophylaxis in a general medicine ward of a university hospital. METHOD: In the analysis, the use of the proper prophylactic dose at the correct time, the use in patients with contraindications, and the misuse in patients without risk of venous thromboembolism were considered. RESULTS: A total of 245 patients were evaluated. Of these patients, 104 (42.4%) were considered to be at risk, and 82.7% either received adequate prophylaxis (i.e., the correct dose at the right time) or did not receive prophylaxis because it was contraindicated. Among the 141 patients who were not at risk, 81 (57.4%) incorrectly received prophylaxis, the majority (61/81) of whom presented with risk factors but did not demonstrate reduced mobility. Among the entire group, only 59.6% of patients were properly treated. CONCLUSIONS: The evaluation of prophylaxis adequacy should consider not only whether the correct dose is administered at the correct time but also whether it is used in patients with contraindications and whether it is inappropriately administered to patients who are not at risk.